The impact of currency carry trade activity on the transmission of monetary policy - Maximilian Boeck; Alina Steshkova; Thomas Zörner (Oesterreichische Nationalbank (OeNB), 2024)
This paper examines how carry trade activity affects the transmission of monetary policy in currency markets. It analyzes a set of developed and emerging market currencies against the U.S. dollar. The U.S. dollar appreciates in response to a conventional monetary policy shock but depreciates to a central bank information shock. A threshold vector autoregressive model is fitted to discriminate between different regimes of speculative carry trade activity. Higher carry trade intensity is associated with larger excess returns and higher crash risk. Across regimes, the differences in exchange rates are mild, while those in interest rates are more pronounced. A currency trading strategy created on the day of central bank announcements, which takes into consideration the joint co-movement of interest rates and stock prices, substantially outperforms the carry trade in terms of the Sharpe ratio and downside risk.
Keywords: C24; C32; E52; F31; F41; 330; Currency markets; Carry Trade Strategy; Monetary Policy; Threshold VAR